Deregulation, competition, and consolidation: The case of the German interurban bus industry - Niklas S. Dürr; Sven Heim; Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
We provide an empirical assessment of the German interurban bus industry two years after its deregulation in January 2013. In addition to a general description of key developments of the industry, we use a unique route-level price data set to study both competitive interaction in general and the potential price effects of a recently announced merger of the two largest players in the market in particular. We find that route-level average prices, inter alia, do not only depend on the number of competitors but especially on the composition of firms operating on a particular route. Although our empirical results suggest short-term price increases on certain route types post-merger, it remains an open question whether the merger should be classified as anticompetitive.
urn:nbn:de:bsz:180-madoc-397362
Keywords: L11; L41; L92; K21; K23; 330; deregulation; competition; merger; interurban bus services; Germany